Famílias camaleão: adaptações, mudanças e desafios da homoparentalidade - Temperini, Carlos Augusto Teixeira (2018)
The aim of this study is to describe and analyze contents and discourses about gay families in the Brazilian and American context in order to understand their arrangements and experiences. The theory structure was based on John Bowlby, Donald Winnicott and Elisabeth Badinter’s studies to discuss the parenthood importance in infant and child development as well as a reflection on “the myth of motherhood" and its impact on gay parenting experiences. The methodology was structured involving both quantitative and qualitative methods. Part of the data collection was carried out in Brazil and the other part the United States of America. For the treatment of quantitative data, we used statistical analysis, and for qualitative research, we used the Grounded Theory. The sample of this study was collected in three stages: (i) gathering public opinion through an online questionnaire about samesex marriage, gay families and child development; (ii) gathering the perception of gay families through a closed-interview questions and (iii) gathering the perception of gay families through an in-depth and open-ended interview. The samples of quantitative research were compounded by 1,055 Brazilians and 180 Americans. The qualitative research sample was compounded by 9 American gay families and 11 Brazilian gay families. It was observed in the American and Brazilian context that gay families, in the perception of the participants, have little social acceptance. These results camouflage the prejudice and discrimination of some of the participants who are self-entitled in favor of diversity, but who blame society for the difficulty of acceptance of those families. The (qualitative and quantitative) data crossing opened the door to understanding the dynamic functioning of gay families, which were called the Chameleon Families: adaptations, changes and challenges of gay families. It has been found that there is a functioning permeated by multiple and dynamic processes, fueled by psychological experiences, interrelated and lived by gay families, characterized by stages that require adaptations, changes and constant challenges. Those families commonly adapt and change because they want to have the right to be a family, to display love without being judged, to build their homes and to have children. They want to occupy social spaces without questions about parental capacity, about the child's mother, and the feeling that every child needs to have a woman present to guarantee their safe development. They want to claim their rights for freedom, equality and equity. They want social justice, so they do not have to invest too much in their children’s protection